1991
DOI: 10.1016/s0006-3495(91)82102-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutations affecting agonist sensitivity of the nicotinic acetylcholine receptor

Abstract: The nicotinic acetylcholine receptor (AChR) is a pentameric transmembrane protein (alpha 2 beta gamma delta) that binds the neurotransmitter acetylcholine (ACh) and transduces this binding into the opening of a cation selective channel. The agonist, competitive antagonist, and snake toxin binding functions of the AChR are associated with the alpha subunit (Kao et al., 1984; Tzartos and Changeux, 1984; Wilson et al., 1985; Kao and Karlin, 1986; Pederson et al., 1986). We used site-directed mutagenesis and expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(106 citation statements)
references
References 37 publications
8
94
1
3
Order By: Relevance
“…Do~-response curves for agonist (Fig. 3) indicated that mutation of %'187 into F resulted in a 10-fold decrease in ACh apparent affinity (Table i), a result which is in good agreement with the recently described mutation of the homologous residue from mouse muscle nicotinic receptor a-subunit [8].…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Do~-response curves for agonist (Fig. 3) indicated that mutation of %'187 into F resulted in a 10-fold decrease in ACh apparent affinity (Table i), a result which is in good agreement with the recently described mutation of the homologous residue from mouse muscle nicotinic receptor a-subunit [8].…”
Section: Resultssupporting
confidence: 89%
“…As observed for mutations near amino acid Y187 in mouse muscle receptor [8], several mutations near Y92 and W!48 of the ~7-subunit, like $94N and WI53F (Fig. 2), G82E and GI51D (not shown), did not cause significant changes on the physiological properties of the receptor.…”
Section: The Competitive Antagonists Dhflesupporting
confidence: 57%
See 1 more Smart Citation
“…This tyrosine is on the C-loop and is close to the pair of adjacent cysteine residues (C192 and C193) that characterises α subunits. The mutation Y190F (like Y93F and W149F) also decreases macroscopic ACh binding (Tomaselli et al, 1991), and increases the EC 50 by 184-fold (in embryonic mouse muscle receptor, Chen et al, 1995). These effects were originally attributed to changes in the binding.…”
Section: Some Well-characterised Mutationsmentioning
confidence: 99%
“…As mentioned, mutations of the MBTA and DDF-labelled Cysi92 and 193 into serines, interfere with a-bungarotoxin binding and with the response to acetylcholine . Also, in the same domain mutation of Tyri9O into Phe yields a receptor which requires more than 50-fold higher concentration of acetylcholine for channel activation than wild type channels with the correlative decrease of agonist-binding affinity (Tomaselli et al 1991).…”
Section: Site Directed Mutagenesis Of the Amino Acids Identified By Amentioning
confidence: 99%